Ventriculoperitoneal shunt placement in poor-grade patients with chronic normal pressure hydrocephalus after aneurysmal subarachnoid haemorrhage. (2nd January 2016) - Yu, Hai; Yang, Min; Zhan, Xiaobo; Zhu, Yu; Shen, Jian; Zhan, Renya
Abstract: Objective : The aim of this study was to analyse the shunt placement in patients who had normal pressure hydrocephalus after poor-grade aneurysmal subarachnoid haemorrhage (aSAH). Methods : Patients diagnosed with NPH after poor-grade aSAH were divided into a treatment group and control group, based on whether they had received ventriculoperitoneal shunt placement. The treatment group was then divided into an improvement group and non-improvement group according to their recovery. The Glasgow Outcome Scale and Mini Mental Scale Examination were used for 3 month and 1 year follow-up rehabilitation measures. Results : Of the 46 total patients, significant improvement was observed at the 3 month and 1 year follow-ups ( p < 0.01) after shunt implantation in the treatment group compared to the control group. Furthermore, patients who were younger ( p = 0.022), had better neurological function (higher Glasgow Coma Score, p < 0.01) and less severe hydrocephalus (lower EI, p < 0.01) appears to be more likely to benefit from the shunt. Conclusions : Patients who had NPH due to poor-grade aSAH would benefit from shunt placement when given the correct candidates and timely management of shunt malfunction. Additionally, the curative effect of the shunt should have been regarded as a long-term goal of rehabilitation in these patients.